1985
DOI: 10.1029/jb090ib14p12503
|View full text |Cite
|
Sign up to set email alerts
|

Neogene tectonic rotation of the Santa Ynez Range, Western Transverse Ranges, California, Suggested by paleomagnetic investigation of the Monterey Formation

Abstract: A paleomagnetic investigation was conducted on dolomite beds in the middle and upper Miocene Monterey Formation in order to determine the timing and amount of post‐early Miocene tectonic rotation experienced by the Santa Ynez Range (part of the western Transverse Ranges province of California). Five stratigraphic sections of the Monterey Formation exposed along the coastline west of Santa Barbara were extensively sampled. The sections were correlated using tuff beds, and ages were assigned to each dolomite bed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 39 publications
4
62
0
Order By: Relevance
“…These stron-tium and foraminiferal data do not contradict these landwardyounging hypotheses; instead when viewed in the context of the early Tertiary paleogeography they suggest that landward younging took place over a very complex late Oligocene and early Miocene topography. This complexity is outlined in detail in the discussions of Vaqueros lithofacies that follow and has been alluded to by previous workers (Hornafius, 1985;Rigsby, 1989aRigsby, , 1994a.…”
Section: Chronostratigraphymentioning
confidence: 99%
See 3 more Smart Citations
“…These stron-tium and foraminiferal data do not contradict these landwardyounging hypotheses; instead when viewed in the context of the early Tertiary paleogeography they suggest that landward younging took place over a very complex late Oligocene and early Miocene topography. This complexity is outlined in detail in the discussions of Vaqueros lithofacies that follow and has been alluded to by previous workers (Hornafius, 1985;Rigsby, 1989aRigsby, , 1994a.…”
Section: Chronostratigraphymentioning
confidence: 99%
“…Hypothetical chronostratigraphy of the Vaqueros Formation. The hypothetical time lines (T1 is older, T2 is younger) are based on the strontium isotope ages reported in this study, on the Vaqueros age ranges reported by Dickinson and others (1987), and on geological evidence (such as the positions of paleoshorelines) presented in this paper and in work by Howard (1988), Hornafius (1985), and others. As discussed in the text, this hypothesis suggests that the Vaqueros Formation decreases in age in all landward directions.…”
Section: Shoreline Sandstones and Conglomeratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Paleomagnetic declination data indicate that the western Transverse Ranges Province block underwent Neogene clockwise transrotation of as much as 100˚ in some western parts beginning no later than 16 Ma (Hornafius, 1985;Morris and others, 1986;Luyendyk and Hornafius, 1987;Liddicoat, 1990;Luyendyk, 1990) and continues to rotate today (Molnar and Gipson, 1994). The more-or-less fixed rotational hub is at the east end of the block, about 25 km east of this study's northwest sector.…”
Section: Paleomagnetic Declinations and Transrotation-northwest Sectormentioning
confidence: 99%